(untitled) (Bangladesh Journal of Otorhinolaryngology, 2022)
Background: Endoscope and microscope are exclusively used in different middle ear pathologies as well as patients with attic cholesteatoma. However, straightforward information regarding surgical advances, postoperative results, and information about in which patients and how this surgical technique should be exclusively used is debatable. Aim: To compare the outcome of primary exclusive endoscopic ear surgery with those of the microscopic ear surgery in two groups of patients with cholesteatoma limited to the attic region. Methods: This prospective observational study was conducted in the Department of Otolaryngology-Head and Neck Surgery, BSMMU, Dhaka, from July 2018 to December 2019, with 26 patients having cholesteatoma limited to the attic region. Patients were divided into two groups. One group of patients were submitted to atticotomy with tympanoplasty via microscopic ear surgery (MES) and a second group to exclusive trans-canal endoscopic ear surgery (EES). All the patients were followed up post-operatively up to 3 months with PTA. Results: Mean bone conduction threshold, air conduction threshold, and ABG has been reduced considerably in both groups (endoscopic and microscopic) at the end of three months postoperatively.There was no significant statistical difference between the two groups in terms of graft uptake success rate and the audiological success rate (p-value >0.05).Postoperatively, pain requiring analgesics wassignificantly lower (p<0.033) in theendoscopic group (23.1%) than in the microscopic group (69.2%). Conclusion: Audiological outcome and graft uptake success rates achieved by the endoscopic ear surgery were similar to the results obtained by the microscopic ear surgery in limited attic cholesteatoma. Bangladesh J Otorhinolaryngol 2022; 28(1): 103-111